Physiological effect of Debt Burden on Individual Business Owners, E_ commerce and its Business Growth - Haitao Sun (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
The objective of this study is to examine the psychological effect of debt burden on owners’ attitude, owner’s performance, owner’s seriousness, and E-commerce and its business growth. To achieve this objective, the relationship between the psychological effect of debt burden, owners’ attitude, owner’s performance, owner’s seriousness, and E-commerce and its business growth was examined in this study. A survey was used in this study in which a questionnaire was used, and data were collected from individual business owners from China. Statistical tool; Partial Least Square (PLS) was used to analyze the data. It is found that the physiological effect of debt burden has major consequences with respect to E-commerce and its business growth. An increase in the debt burden increases E-commerce and its business growth. The psychological effect of debt burden also has a major role in owners’ attitude, owner’s performance, and owner’s seriousness. Furthermore, owners’ attitude, owner’s performance, and owner’s seriousness have a positive effect on E-commerce and its business growth.